Pengaruh Perceived Quality dan Brand Image dalam Keputusan Memilih Kuliah dengan Brand Trust Sebagai Varibael Intervening - Muhammad Caesar Akbar; Syaifuddin; Fajar Rezeki Ananda Lubis (Universitas Muhammadiyah Surabaya, 2025)
AbstractThe selection of a campus in achieving the goal of college certainly has many determining factors. So it is necessary to explore what are the reasons. This study will test whether there is an influence of Perceived Quality and Brand Image in determining the selection of the destination campus. Data collection used in this study is associative research and literature review. Data collection was carried out at six Aviation Polytechnics in Indonesia. The results of the study showed that there was a significant influence of Perceived Quality and Brand Image on Brand Trust. Furthermore, Perceived Quality also influences the Decision to Choose College and so does Brand Image have an influence on the Decision to Choose College. Furthermore, Brand Trust also has a Significant Influence on the Decision to Choose College. Furthermore, there is the Influence of Perceived Quality Through Brand Trust on the Decision to Choose College. The findings also show that there is an influence of Brand Image Through Brand Trust on the Decision to Choose College. So it is concluded that Perceived Quality and Brand Image are part of the factors that determine the selection of the campus that is the destination in college. Keyword: Perceived Quality, Brand Image, Destination Campus, Indonesian Aviation Polytechnic.